Upregulation of circulating inflammatory biomarkers under the influence of periodontal disease in rheumatoid arthritis patients. (July 2020) - Panezai, Jeneen; Ali, Azra; Ghaffar, Ambereen; Benchimol, Daniel; Altamash, Mohammad; Klinge, Bjӧrn; Engström, Per-Erik; Larsson, Anders
Highlights: Periodontal disease (PD) profoundly increases the overall systemic inflammatory 'score' in RA. Disease activity is associated more frequently with inflammatory biomarkers in the presence of PD. A vast array of biomarker analysis contributes to understanding inflammatory diseases. Timely diagnosis of PD is crucial in planning RA therapy. Abstract: Objectives: Periodontal disease (PD) and rheumatoid arthritis (RA) are chronic immuno-inflammatory conditions with osteolysis being a hallmark feature. The influence of PD on RA's systemic inflammatory status and disease activity remains unclear. The objective of this study was to assess the systemic inflammation and disease activity of RA under the influence of PD. Methods: In this case-control study, 38 RA patients (19 with PD and 19 without PD) were compared to 38 non-RA patients and 12 healthy controls. Periodontal parameters (bleeding on probing (BOP), probing pocket depth (PPD), PPD Total, PPD Disease and marginal bone loss (MBL) were determined. Serological analyses included quantification of 92 inflammatory biomarkers using a multiplex proximity extension assay, anti-citrullinated protein antibodies (ACPA), rheumatoid factor (IgM-RF) and erythrocyte sedimentation rate (ESR). RA disease activity was determined using Disease Activity Score for 28 joints (DAS28). All RA patients were on medication. Results: IgM-RF was higher in RA patients with PD. PD conditions were more severe in the non-RA group. Inflammatory biomarkers (IL-10RB, IL-18, CSF-1, NT-3, TRAIL, PD-L1, LIF-R, SLAMF1, FGF-19, TRANCE, CST5, STAMPB, SIRT2, TWEAK, CX3CL1, CXCL5, MCP-1) were significantly higher in RA patients with PD than RA without PD. DAS28 associated with twice as many inflammatory biomarkers in RA patients with PD whereas IgM-RF and ACPA associated more frequently with biomarkers in the RA without PD group. IgM-RF correlated inversely with BOP. Conclusion: Periodontal disease augments systemic inflammation in RA. A profound influence exists independent of autoimmune status.